Pemanfaatan Copper Slag Sebagai Substitusi Semen Pada Campuran Beton Mutu K225 - Muhammad Kadhafi (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2015)
Concrete is a construction material that is widely used in building structures work in Indonesia because of the many benefits provided such as its constituent materials are easy to obtain, easy to set up, able to carry a heavy burden, resistant to high temperatures, and small maintenance cost. Various research efforts have been made in order to make progress in concrete technology due to the limited availability of material using other similar materials that reduce the use of cement. Efforts are made to the terms of the utilization of copper slag from P.T. Smeltng Gresik. Steps being taken in this research is the study of literature, material preparation and testing materials at the Concrete and Materials Laboratory, Department of Civil Engineering Faculty of Engineering, University of Sriwijaya. Then proceed with the manufacture of cylindrical specimen measures 15cm x 30cm with a variety of copper slag reimbursement by 0%, 10 %, 15%, 20% and 30% of the partial cement that is was used to planning the compressive strength of fc’ 18,675, and then testing concrete compressive strength From the analysis it can be concluded that The results showed that copper slag as a cementitious can have a positive impact on the quality of concrete , namely the variation of 15 % copper slag increased optimum compressive strength (20,06 %) compared to concrete without using a variation of copper slag.